Comparing Fever Management by Mothers of Children Aged 1–5 and 6–10 Years - Burcu Korkut, Pinar Kalem, Elif Musellim, Habibe Inci, Erkan Doğan, Didem Adahan, (Pakistan Journal of Medical & Health Sciences, 2022)
Background/Aim: This study aimed to compare the fever management by mothers of children aged 1-5 and 6-10 years admitted with fever. Methods: This cross-sectional and descriptive study was conducted between November 2021 and March 2022 at Karabük University Department of Pediatrics and Karabük City Family Health Centers. To work, 710 mothers with febrile children between 1-5 and 6-10 participated. Due to 58 invalid questionnaires, 652 mothers formed the study population. All mothers were included in the study without sample selection. A questionnaire consisting of 3 parts and 33 questions was applied to the participants face-to-face. Questions; It consisted of the first sociodemographic part such as age, gender, mother's education level, the second part measuring the knowledge, attitudes, and behaviors of mothers about fever symptoms, and the third part consisting of the Turkish Version of the Parental Fever Management Scale (PFMS-TR). Results: Mothers of 332 children between the ages of 1-and 5 and 324 children between the ages of 6-and 10 participated in the study. The rate of girls between the ages of 1-and 5 was 57.8% (n=192), and the rate of girls between the ages of 6-and 10 was 49.4% (n=160). There was no significant difference between the two participant groups regarding PFMS-TR (p=0.198). In those who applied to the hospital with the complaint of fever (p=0.004), who received training from health professionals about what to do in case of fever in their child (p=0.001), understanding that their child has a fever from body temperature or skin contact (p=0.001), applying to a health institution in the presence of fever (p=0.001), determining body temperature requiring antipyretic (p<0.001) and administering antipyretic drugs according to doctor's prescription (p<0.001) a statistically significant difference was found between the mothers of two groups of children with fever. Conclusion: It was determined that there was no difference between the mothers' fever-related anxiety and phobia levels in both groups. This situation, regardless of the age group in which the fever symptom occurs, can be explained by the parents' anxiety. So, it is essential to carry out education programs to inform mothers about fever management accurately and adequately to reduce the level of anxiety they experience.